Studi Alquran dan Integrasi Keilmuan: Studi Kasus UIN Sunan Gunung Djati Bandung - Syahrullah Iskandar (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2016)
Quranic studies constitute a basis for developing Islamic studies. Quranic studies support the concept of integration of knowledge by accommodating the scientific findings into the revealed Qur’anic dimension. This article investigates the role of Qur’anic studies in the process of knowledge integration and its application at Ushuluddin Faculty, State Islamic University, Bandung. This article shows that in term of curricula and methods of learning, Ushuluddin Faculty provides accommodative response to the knowledge integration model. Some notes to be considered, however, is to include dynamic and progressive method of understanding the Qur’an in relation to current situation in reality. Thus, an approach ‘from reality to the text’ in studying the Qur’an is required to accommodate the concept of knowledge integration.